Hubungan antara Fear of Missing Out dengan Kecanduan Media Sosial - Nafisa, Salwa; Kusuma Salim, Irma (UIR Press, 2022)
This study aims to determine the relationship between Fear of Missing Out and social media addiction in stdents at the Islamic University of Riau. The hypothesis in this study is positive and significant relationship between fear of missing out and social media addiction in student at the Islamic University of Riau. Subjects in this study amounted to 100 people who are student with age range of 19-25 years. Data collection uses a fear of missing out scale of 21 items and a social media addiction items. The analytical method used in this research is Spearman Rank Order correlation analysis. The results of statistical analysis obtained a correlation value of 0.264 (>0.05) with a significan 0.008 (p<0.05). The result of this tudy obtained a value of R = 0.304 with p < 0.005 which is 0.092, this indicates that there is a significant positive relationship between fear of missing out and sosial media addiction in students at the Islamic University of Riau. That is, the higher the addiction to social media, the higher the fear of missing out and vice versa. The effeictive contribution of the social media addiction provides and active contribution of 9.2% to the fear of missing out variable while the rest is influenced by other factors.